"That's when the relationship shifted": Relational and communicative turning points in Alzheimer's disease and related dementias. Issue 1 (19th November 2021) - Cooper, R. Amanda; Pitts, Margaret J.; Harwood, Jake
Abstract: This study investigated the relational turning points experienced by caregiving spouses across the trajectory of Alzheimer's disease and related dementias. Data were collected using a modified version of the retrospective interviewing technique which facilitated close analysis of relational turning points and the role of communication in shaping and managing these turning points. Caregiving spouses described nine relational turning points across the disease trajectory. The turning points coalesced under four broad changes in the marital relationship: my spouse has dementia, from spouse to caregiver, my spouse is gone, and transcending dementia through love. Participants used five communication strategies to manage their relationships: having open and intimate conversations, avoiding confrontation, avoiding bringing attention to symptoms, engaging in daily conversations and activities, and communicating love and affection. Findings reveal the specific turning points that mark relational change across the disease trajectory and caregiving spouses' strategies to maintain their relationship through this prolonged end‐of‐life transition.